TYPES OF PEDAGOGIC INFORMATION FOR THE DEVELOPMENT OF SKILLS RELATED TO THE USE OF FRENCH PAST TENSE VERB FORMS - Аліна Андрущенко (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The author built the types of pedagogic information to develop the programme to teach the usage of the most frequent French past tense verb forms in oral and written speech to students of Linguistic Higher Educational Institutions (faculties), analyzed the selection criteria of all the types of pedagogic information, as well as selected the authentic French texts to provide for the said programme, gave the examples of exercises aimed at the formation of skills related to the use of the past tense verb forms.